Characterization of Adverse Events Detected in a Large Health Care Delivery System Using an Enhanced Global Trigger Tool over a Five‐Year Interval. (13th March 2014) - Kennerly, Donald A.; Kudyakov, Rustam; da Graca, Briget; Saldaña, Margaret; Compton, Jan; Nicewander, David; Gilder, Richard
<x xml:space="preserve">Abstract</x> Objective To report 5 years of adverse events (AEs) identified using an enhanced Global Trigger Tool (GTT) in a large health care system. Study Setting Records from monthly random samples of adults admitted to eight acute care hospitals from 2007 to 2011 with lengths of stay ≥3 days were reviewed. Study Design We examined AE incidence overall and by presence on admission, severity, stemming from care provided versus omitted, preventability, and category; and the overlap with commonly used AE‐detection systems. Data Collection Professional nurse reviewers abstracted 9, 017 records using the enhanced GTT, recording triggers and AEs. Medical record/account numbers were matched to identify overlapping voluntary reports or AHRQ Patient Safety Indicators (PSIs). Principal Findings Estimated AE rates were as follows: 61.4 AEs/1, 000 patient‐days, 38.1 AEs/100 discharges, and 32.1 percent of patients with ≥1 AE. Of 1, 300 present‐on‐admission AEs (37.9 percent of total), 78.5 percent showed NCC‐MERP level F harm and 87.6 percent were "preventable/possibly preventable." Of 2, 129 hospital‐acquired AEs, 63.3 percent had level E harm, 70.8 percent were "preventable/possibly preventable"; the most common category was "surgical/procedural" (40.5 percent). Voluntary reports and PSIs captured <5 percent of encounters with hospital‐acquired AEs. Conclusions AEs are common and potentially amenable to prevention. GTT‐identified AEs are seldom caught by commonly used AE‐detection systems.